2019
DOI: 10.24815/jipi.v3i2.14847
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Bahan Ajar Bermuatan Konteks Kelautan Untuk Meningkatkan Literasi Sains Siswa

Abstract: Literasi sains siswa Indonesia masih rendah dan buku yang selama ini digunakan belum melatih siswa untuk memahami hakekat sains. Oleh karena itu, literasi sains siswa perlu ditingkatkan melalui bahan ajar yang menyajikan fenomena alam dan permasalahan yang terjadi di sekitar siswa. Tujuan penelitian adalah mengembangkan bahan ajar bermuatan konteks kelautan untuk meningkatkan literasi sains siswa. Penelitian ini merupakan pengembangan dengan metode four step material teaching development. Efektivitas bahan aja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
1
9
0
1
Order By: Relevance
“…Students become accustomed to thinking processes and scientific activities, resulting in increased mastery of concepts and competencies. This is consistent with Puspitasari et al [23], who found that context-based inquiry learning can improve students' conceptual proficiency. Students are adept at bridging the gap between everyday experiences and classifying and organizing the subject matter.…”
Section: Resultssupporting
confidence: 91%
“…Students become accustomed to thinking processes and scientific activities, resulting in increased mastery of concepts and competencies. This is consistent with Puspitasari et al [23], who found that context-based inquiry learning can improve students' conceptual proficiency. Students are adept at bridging the gap between everyday experiences and classifying and organizing the subject matter.…”
Section: Resultssupporting
confidence: 91%
“…The result shows that the students in learning are merely memorizing the material without understanding them whereby understanding, the concepts will be long stored. Another factor that causes low concept mastery is that the teachers do not design contextual learning according to students' expertise competencies (Padwa, et al, 2019;Pursitasari, et al 2019). It also causes students to easily forget (Krathwohl, 2002).…”
Section: Figure 3 the Results Of Concept Mastery Test By Vocational Studentsmentioning
confidence: 99%
“…These aspects lead to how the module presents concepts scientifically, has novelty, and trains scientific literacy skills. According to Puspitasari et al (2019), teaching materials should have the following characteristics:…”
Section: The Feasibility Of the Modulementioning
confidence: 99%